2016
DOI: 10.3402/gha.v9.32116
|View full text |Cite
|
Sign up to set email alerts
|

Seasonality of hospital admissions for mental disorders in Hanoi, Vietnam

Abstract: BackgroundSome studies have shown a relationship between seasonality in weather patterns and depressive and behavioural disorders, especially in temperate climate regions. However, there is a lack of studies describing the seasonal patterns of hospital admissions for a variety of mental disorders in tropical and subtropical nations. The aim of this study has been to examine the relationship between seasons and daily hospital admissions for mental disorders in Hanoi, Vietnam.DesignsA 5-year database (2008–2012)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 39 publications
(72 reference statements)
0
13
1
1
Order By: Relevance
“…[ 14 ] In an analysis from a mental hospital of Vietnam, a positive association between temperature and admissions for mental disorders and substance abuses in the month of June when the weather is at its hottest has been reported. [ 15 ] However, in our study, these cases were observed in majority during monsoon and autumn (July to November). Probably because in Himachal Pradesh during sowing and cutting of rabi and kharif crops, people are busy and the attendants of patients with neuropsychiatric disorders generally postpone their visit to health centers.…”
Section: Discussioncontrasting
confidence: 64%
“…[ 14 ] In an analysis from a mental hospital of Vietnam, a positive association between temperature and admissions for mental disorders and substance abuses in the month of June when the weather is at its hottest has been reported. [ 15 ] However, in our study, these cases were observed in majority during monsoon and autumn (July to November). Probably because in Himachal Pradesh during sowing and cutting of rabi and kharif crops, people are busy and the attendants of patients with neuropsychiatric disorders generally postpone their visit to health centers.…”
Section: Discussioncontrasting
confidence: 64%
“…The effect of seasonality in the hospital admission rate and LoS has been reported by many studies. [28][29][30][31][32] In our study, there were more admissions during month of March(10.2%) as compared to other months. The length of stay was maximum(21.8 days) in May and minimum(17.7 days) in March and there was significant association of LoS with month of admission.…”
Section: Discussionmentioning
confidence: 42%
“…This was consistent with most of the previous studies of a similar nature. Studies from Shanghai [ 8 ], Adelaide, Australia [ 10 , 12 ], Brisbane, Australia [ 44 ], and Vietnam [ 15 ] also reported a higher relative risk for the older group at warmer temperatures. Some studies, however, reported a higher risk among younger groups, including studies from Toronto [ 9 ] and Adelaide, Australia [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies from Shanghai and Toronto [ 8 , 9 ], two Northern Hemispheric cities located at high latitudes above the Tropic of Cancer (23°26′12.9″), have reported higher relative risks of mental-disorder admissions at warmer temperatures, but no association at low temperatures. A majority of other studies also reported a higher risk of mental disorders during warmer temperatures but they focused on hot seasons only [ 10 , 11 ], were conducted during heat waves [ 12 , 13 , 14 ], looked at the effect of seasonality [ 15 , 16 ], used statistical methods not capable of revealing non-linear and lagged effects [ 17 , 18 ], or were not population-based [ 19 ]. Suicide rate, which is relevant to mental disorders, has also been found increasing with warmer temperatures [ 20 , 21 , 22 ] in different regions.…”
Section: Introductionmentioning
confidence: 99%